A highly sensitive "turn‐on" fluorescent sensor for the detection of human serum proteins based on the size exclusion of the polyacrylamide gel. Issue 4 (2nd December 2013) - Xu, Shenghao; Liu, Pingping; Lu, Xin; Zhang, Jing; Huang, Lingyun; Hua, Wenhao; He, Dacheng; Ouyang, Jin
<x xml:space="preserve">Abstract</x> A highly sensitive "turn‐on" fluorescent sensor based on the size exclusion of the polyacrylamide gel was developed for the on‐gels detection of human serum proteins after PAGE. The possible mechanism of this fluorescence sensor was illustrated and validated by utilizing five kinds of colloidal silver nanoparticles with different particle size distribution and six kinds of polyacrylamide gels with different pore size. It was attributed to that silver nanoparticles (<5 nm in diameter) had been selectively absorbed into the gel and formed the small silver nanoclusters, resulting in the red fluorescence. Using this new technique for the detection of human serum proteins after PAGE, a satisfactory sensitivity was achieved and some relatively low‐abundance proteins (e.g. zinc‐alpha‐2‐glycoprotein), which are the significant proteinic markers of certain diseases can be easily detected, but not with traditional methods. Furthermore, it was also successfully applied to distinguish between serums from hepatoma patient and healthy people. As a new protein detection technique, the colloidal silver nanoparticles based "turn‐on" fluorescent sensor offers a rapid, economic, low background, and sensitive way for direct detection of human serum proteins, showing available potential and significance in the development of nanobiotechnology and proteome research.